La théorie et la pratique de l’Arms Control : Bilan et perspectives - Klein, Jean (Études internationales, 1989)
Arms control, as developed by American civilian strategists in the late 1950s, sought to maintain the equilibrium upon which mutual deterrence was dependent, and strove to prevent direct conflict between the two nuclear protagonists. Has it exhausted its virtuality and will there be a return to the tradition of general and total disarmament? One comes to ask within the framework of this analysis, whether the Washington treaty of december 1987 introduces a new element to arms control, or whether it closely follows the methods used in former agreements. In an effort to better comprehend this question, the past experiences in arms control will be examined before making any conjectures on its anticipated evolution, all the while taking into consideration the new approaches used in the American-Soviet relations, the problems created by technological innovation, and the intentions of both the small and medium States.